TDP‐43 loss of function inhibits endosomal trafficking and alters trophic signaling in neurons. (12th September 2016) - Schwenk, Benjamin M; Hartmann, Hannelore; Serdaroglu, Alperen; Schludi, Martin H; Hornburg, Daniel; Meissner, Felix; Orozco, Denise; Colombo, Alessio; Tahirovic, Sabina; Michaelsen, Meike; Schreiber, Franziska; Haupt, Simone; et al.
Abstract: Nuclear clearance of TDP‐43 into cytoplasmic aggregates is a key driver of neurodegeneration in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD), but the mechanisms are unclear. Here, we show that TDP‐43 knockdown specifically reduces the number and motility of RAB11‐positive recycling endosomes in dendrites, while TDP‐43 overexpression has the opposite effect. This is associated with delayed transferrin recycling in TDP‐43‐knockdown neurons and decreased β2‐transferrin levels in patient CSF. Whole proteome quantification identified the upregulation of the ESCRT component VPS4B upon TDP‐43 knockdown in neurons. Luciferase reporter assays and chromatin immunoprecipitation suggest that TDP‐43 represses VPS4B transcription. Preventing VPS4B upregulation or expression of its functional antagonist ALIX restores trafficking of recycling endosomes. Proteomic analysis revealed the broad reduction in surface expression of key receptors upon TDP‐43 knockdown, including ErbB4, the neuregulin 1 receptor. TDP‐43 knockdown delays the surface delivery of ErbB4. ErbB4 overexpression, but not neuregulin 1 stimulation, prevents dendrite loss upon TDP‐43 knockdown. Thus, impaired recycling of ErbB4 and other receptors to the cell surface may contribute to TDP‐43‐induced neurodegeneration by blocking trophic signaling. Synopsis: TDP‐43 loss of function as seen in ALS and FTLD inhibits trafficking of recycling endosomes in rat and human neurons. Impaired recycling to the cell surface inhibits trophic signaling of ErbB4 and other receptors. TDP‐43 knockdown inhibits motility of recycling endosomes in dendrites by inducing the expression of VPS4B, an ESCRT disassembly factor, and direct binding partner of ALS gene CHMP2B (ALS17/FTD3). Trafficking of recycling endosomes is rescued by knockdown of VPS4B or overexpression of its antagonist ALIX. TDP‐43 knockdown or VPS4B overexpression delays recycling of ErbB4 (ALS19) and other receptors and adhesion molecules to the cell surface. Dendrite loss upon TDP‐43 knockdown is rescued by the expression of ErbB4, but not its ligand NRG1, indicating that the loss of TDP‐43 inhibits trophic signaling. We find evidence for an impaired recycling endosome function in ALS/FTLD brain and CSF. Abstract : The loss of TDP‐43 function, as often seen in neurodegenerative diseases, blocks trafficking of recycling endosomes and impairs the proper localization of cell surface receptors.